Islam in German East Africa, 1885–1918 - Haustein, Jörg. author. aut Link
XVI, 435 p. 27 illus.
Keywords: In this rich and multi-layered deconstruction of German colonial engagement with Islam, Jörg Haustein shows how imperial agents in Germany’s largest colony wielded the knowledge category of Islam in a broad set of debates, ranging from race, language, and education to slavery, law, conflict, and war. These representations of ‘Mohammedanism’, often invoked for particular political ends, amounted to a serious misreading of Muslims in East Africa, with significant long-term effects. As the first in-depth account of the politics of Islam in German East Africa, the book makes an essential contribution to the history of religion in Tanzania before British rule. It also offers a template for re-reading the colonial archive in a manner that recovers Muslim agency beyond a European paradigm of religion. Jörg Haustein is Associate Professor of World Christianity at the University of Cambridge and a Fellow of Selwyn College, Cambridge. Previously, he has taught at the School of Oriental and African Studies in London and the University of Heidelberg in Germany. He is a scholar of religion in Africa from the nineteenth century onward, specializing in Pentecostal Christianity, colonial Islam, and the intersection of religion and development.